Revolutionizing Retail Transactions with Scalable UI Architectures - Harish Musunuri, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The retail industry is undergoing a transformative shift as organizations evolve from legacy transaction processing systems toward cloud-native architectures. This technical article explores how modern, event-driven UI architectures are revolutionizing retail operations by addressing critical limitations of traditional systems. Legacy infrastructures characterized by tightly coupled monolithic designs create fragmented customer experiences, impose scalability constraints, perpetuate vendor lock-in, and impede innovation. By contrast, modern architectural approaches featuring decoupled microservices, cross-platform compatibility, event-driven communication patterns, and cloud infrastructure deliver measurable improvements in customer experience, cost optimization, innovation velocity, and business agility. The implementation considerations highlight the importance of phased migration strategies, API-first design principles, security-by-design practices, and comprehensive staff training to maximize successful outcomes.
Keywords: Architecture; Cloud-Native; Microservices; Omnichannel; Scalability